Long non-coding RNA PVT1 as a novel candidate for targeted therapy in hematologic malignancies. (May 2018) - Houshmand, Mohammad; Yazdi, Narjes; Kazemi, Alireza; Atashi, Amir; Hamidieh, Amir Ali; Anjam Najemdini, Ali; Mohammadi Pour, Mahshid; Nikougoftar Zarif, Mahin
Abstract: Cancerous cells show resistance to various forms of therapy, so applying up to the minute targeted therapy is crucial. For this purpose, long non-coding RNA PVT1 as shown by recent studies is an important oncogene that interacts with vital cellular signaling pathways and different proteins such as c-Myc, NOP2 and LATS2. Due to the enormous role of long non-coding RNAs in development of leukemias, we aimed to show the role of PVT1 knock-down on fate of different hematologic cell lines. owing to this matter, various experiments such as Real-time PCR, cell cycle analysis and apoptosis assay were performed. Meanwhile, proliferation rate by CFSE, protein expression of c-Myc and hTERT by western blot and flow cytometry analysis were investigated. Our results demonstrated that PVT1 knock-down results in c-Myc degradation, proliferation down-regulation, induction of apoptosis and G0/G1 arrest. Simultaneously, for the first time, we posited the relation between this oncogene with hTERT that reduced after PVT1 knock-down. Considering these results, long non-coding RNA PVT1 may be a potential option for targeted therapy in hematologic malignancies.